Generalised cost optimisation of short-haul twin-turboprop aircraft including airport considerations - Pant, Rajkumar S. (Cranfield University, 1997)
In this thesis, a methodology is proposed for the conceptual design and optimisation of twin-turboprop Commuter & Regional aircraft suitable for operation over a spe¬cific short-haul route. Using this methodology, the optimum configuration and flight profiles of such aircraft for operation over various stage-lengths can be obtained. By significantly modifying an existing computer code for synthesis and trajectory opti¬misation of Commuter aircraft (CASTOR), a new code (CRAGER) has been developed to estimate the Generalised cost of travel incurred by a passenger for air-travel be¬tween two cities. A new sub-module has been developed for the geometric sizing of a suitable airport as per ICAO/FAA recommendations, and estimation of the Airport cost, i.e. the cost associated with setting-up and operating this airport at one of the two cities. This module is incorporated into CRAGER. Generalised cost is assumed to consist of the Access cost, Flight cost, Time cost and the Airport cost, and is proposed as a new objective function to be minimised. In an exploratory case study, the efficacy of two stochastic optimisation methods viz. Genetic Algorithms (GA) and Simulated Annealing (SA) was demonstrated for handling complicated objective functions related to aircraft conceptual design. In particular, the SIMANN SA code was found to be quite robust and easy to imple¬ment, and came up with better solutions compared to conventional gradient based optimisers for multi-modal objective functions. As an example of the application of the proposed methodology, several case studies were carried out for business travel in India, using both CASTOR & CRAGER. Based on a survey of existing regional airports in India, the airports were classified under three levels, enabling estimation of Airport cost associated with operating a specific aircraft. A model was developed for predicting the demand for business travel in India between a metropolitan city (hub) and another city located near-by (spoke). The case studies revealed the non-linear nature of the airport sub-module, due to the airport classification system followed by ICAO & FAA. It was seen that when the annual travel demand is low, the Generalised cost is dominated by the Airport cost and the Time cost. With increase in annual travel demand, however, the Flight costs dominate the Generalised cost, hence larger aircraft have lower Generalised costs. High-capacity aircraft were seen to have a low Flight cost, but this advantage was more than overcome by the excessively high Airport and Time costs associated with them. Compared to pressurised aircraft, the un-pressurised commuter aircraft suffer from severe penalties due to limitations imposed on their cruising altitude and descent profile. Finally, the optimum 50 seater aircraft obtained by CRAGER had better or marginally lower DOC and Generalised cost compared to existing aircraft.